2019
DOI: 10.1038/s41467-018-07966-5
|View full text |Cite
|
Sign up to set email alerts
|

Fibril formation and therapeutic targeting of amyloid-like structures in a yeast model of adenine accumulation

Abstract: The extension of the amyloid hypothesis to include non-protein metabolite assemblies invokes a paradigm for the pathology of inborn error of metabolism disorders. However, a direct demonstration of the assembly of metabolite amyloid-like structures has so far been provided only in vitro. Here, we established an in vivo model of adenine self-assembly in yeast, in which toxicity is associated with intracellular accumulation of the metabolite. Using a strain blocked in the enzymatic pathway downstream to adenine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 65 publications
(75 reference statements)
3
72
0
Order By: Relevance
“…350 Moreover, the addition of polyphenol inhibitors of amyloid rescued the yeast cells without lowering the level of adenine, indicating that the formation of aggregates, rather than the presence of a high concentration of the metabolite, resulted in the cytotoxicity. 350 As protein amyloid models in yeasts have been extensively explored by many groups flowing the pioneering work of the late Susan Lindquist, 351 the current use of yeast models allows to compare the cellular mechanisms of protein homeostasis (proteostasis) and that of metabolite homeostasis (metabostasis). The yeast system will allow further analysis of the cellular machinery that is involved in the response to abnormal accumulation of metabolites with and without self-assembly into amyloid-like structures.…”
Section: Metabolite Amyloidosismentioning
confidence: 99%
See 1 more Smart Citation
“…350 Moreover, the addition of polyphenol inhibitors of amyloid rescued the yeast cells without lowering the level of adenine, indicating that the formation of aggregates, rather than the presence of a high concentration of the metabolite, resulted in the cytotoxicity. 350 As protein amyloid models in yeasts have been extensively explored by many groups flowing the pioneering work of the late Susan Lindquist, 351 the current use of yeast models allows to compare the cellular mechanisms of protein homeostasis (proteostasis) and that of metabolite homeostasis (metabostasis). The yeast system will allow further analysis of the cellular machinery that is involved in the response to abnormal accumulation of metabolites with and without self-assembly into amyloid-like structures.…”
Section: Metabolite Amyloidosismentioning
confidence: 99%
“…It was recently demonstrated that a yeast model of metabolite aggregation could be constructed. 350 By blockage of adenine salvage pathways, a yeast model in which adenine accumulates was obtained. Feeding these model yeast with adenine exerted a toxic effect in a non-linear sigmoidal-shaped dose-dependent manner.…”
Section: Metabolite Amyloidosismentioning
confidence: 99%
“…Based on our result in the mutant with disrupted HOG signaling pathway, we can add osmotic shock to this list. Yet another possible mechanism is formation of amyloid-like fibrils which has been shown to take place for glycine in vitro (Banik et al, 2016) and for other amino acids both in vitro and in vivo (Shaham-Niv et al, 2015;Laor et al, 2019). It seems likely though that different amino acids are toxic for different reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The adenine accumulation model was therefore established through genetic manipulations of the native yeast metabolism. This was achieved by disrupting the APRT and ADA budding yeast orthologs, APT1 and AAH1 , leading to high intracellular levels of adenine and thereby allowing to best mimic the metabolite accumulation that underlies the pathology of these disorders in vivo (Laor et al, 2019).…”
Section: Adenine Accumulation Yeast Modelmentioning
confidence: 99%